The Effect of Young Coconut Water on Blood Pressure in Hypertensive Patients - Awaluddin; Anelda Pristika (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the effect of young coconut water on reducing blood pressure in hypertensive patients. Method: The quasi-experimental study was conducted in the work area of the Perhentian Luas Public Health Centre, Kuantan Singingi district, Riau province, Indonesia, from June 12 to 26, 2022, and comprised people aged >35 years with stage I hypertension. They were divided into intervention group A and control group B. Group A received young coconut water 150ml for 1 week once a day in the morning. Data was collected using observation sheets and blood pressure monitoring. Data was analysed using SPSS 20. Results: Of the 30 subjects, 15(50%) were each in each of the two groups. All the 15(100%) respondents in group A were females, while there were 10(66.7%) males and 5(33.3%) females in group B. In both the groups, there were 8(53.3%) subjects aged 26-45 years and 7(46.7%) aged >45 years. Systolic and diastolic blood pressure before and after the intervention showed significant difference in group A (p<0.05), while the difference in group B was not significant (p>0.05). Conclusions: Consuming young coconut water every day for 7 days reduced blood pressure in hypertensive patients. Keywords: Cocos, Blood Pressure, Public Health, Hypertension, Diastole.